Men, Work, and Mid-life Crisis: Contextual Biblical Interpretation and the Normativity of the Future in the Pastoral Care of Men - Kummer, Armin M. (Louvain studies, 2024)
This article explores how contextual biblical interpretation and the normativity of the future approach can be fruitfully employed in the pastoral care of professional men. It introduces a gender-specific model of pastoral care of working-age men, which includes the use of biblical texts. A short case study serves as illustration. A contextual interpretation of the Lukan depiction of Simon Peter leads to the cluster of experiences often referred to as 'mid-life crisis'. After a brief review of extant scholarship on mid-life, the fourth section brings the results into critical dialogue with the normativity of the future approach. This article concludes that the normativity of the future approach can provide useful impulses when applied in pastoral conversations about some of the pertinent issues most men encounter during middle age.